Improving the layout of a jobshop by simulation - Le Phan Huu Hieu; Pastijn, Hugo; Huynh, Ngoc Phien; Nagarur, Nagendra N.; Government of Belgium (Bangkok : Asian Institute of Technology, 1996)
The sweeping propensity of merging the economies together into the regional markets or farther, a global market has made the increasing severity of competition inevitable. In such circumstances, the issue of facility layout emerged as the means and the end to help set up from scratch or enhance adaptive capability of an organization without recourse to excessive investment. Many models and algorithms have been developed so far to find out the optimal solution to facility layout problems. However, they are too complex to solve analytically to a satisfactory extent. In light of the advent of computer plus the advantages of simulation technique, there exists a tendency to exploit these powerful tools for the layout problems. The application requires the participation of both analyst and decision maker with the support of some available softwares and allows an evaluation of multi-criterion as wishful thinking. This thesis focuses on establishing the simulated model of current layout of a jobshop in Vietnam using an object-oriented simulation package. This model next is the basis to build · and then to choose the best layout among the Group-Technology-based alternatives, having preliminarily been screened beforehand with a popular layout software.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Advanced Technologies
Thesis (M. Eng.) - Asian Institute of Technology, 1996
Keywords: Plant layout -- Simulation methods